2012
DOI: 10.4067/s0718-95162012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of olive residue and saprophytic fungi on the growth of Verticillium dahliae and its effect on the dry weight of tomato (Solanum lycopersicum L.)

Abstract: The saprophytic fungi Aspergillus niger, Coriolopsis rigida, Fusarium lateritium, F. oxysporum, Mucor racemosus, Paecilomyces farinosus, Penicillium chrysogenum, P. restrictum, Trametes versicolor, Trichoderma harzianum, T. pseudokoningii and T. viride were able to decrease the growth in vitro of Verticillium dahlie in the presence of aqueous extract of olive residue. The conidia number of V. dahliae decreased when grown on aqueous extract of olive residue, autoclaved or filtered through 0.45 micron filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…The ability to suppress VWO by using OM relies on different mechanisms that are yet insufficiently understood. The inhibition of the pathogen's growth may be attributed to biocontrol exerted by specific components of the microbial communities present in the OM and/or that are stimulated upon the addition of the OM to the soil, by means of antibiosis, competition, or parasitism [150,151]. The different physical-chemical properties of OM, such as variations of pH; EC (dS/m); the concentration of K + , Ca + , PPO 4 3 , N-NO 3 -, and N-NH 4 + ; enzymatic diversity; β-glucosidase activity; oxygen uptake rate; or phosphatase activity may influence the effectiveness of OM treatments and may be used as predictors of the suppressive capacity of these composts against V. dahliae [147,152,153].…”
Section: Organic Amendments: a Second Life For Agricultural Waste To mentioning
confidence: 99%
“…The ability to suppress VWO by using OM relies on different mechanisms that are yet insufficiently understood. The inhibition of the pathogen's growth may be attributed to biocontrol exerted by specific components of the microbial communities present in the OM and/or that are stimulated upon the addition of the OM to the soil, by means of antibiosis, competition, or parasitism [150,151]. The different physical-chemical properties of OM, such as variations of pH; EC (dS/m); the concentration of K + , Ca + , PPO 4 3 , N-NO 3 -, and N-NH 4 + ; enzymatic diversity; β-glucosidase activity; oxygen uptake rate; or phosphatase activity may influence the effectiveness of OM treatments and may be used as predictors of the suppressive capacity of these composts against V. dahliae [147,152,153].…”
Section: Organic Amendments: a Second Life For Agricultural Waste To mentioning
confidence: 99%
“…El análisis factorial de las 24 respuestas de ansiedad del ISRA arroja tres factores que coinciden básicamente con los tres sistemas de respuesta de ansiedad (Lang, 1968) (Espada, Torres, Cano-Vindel & Ochoa, 1994;Miguel-Tobal & Cano-Vindel, 1995;Lancha & Carrasco, 2003); trastornos del estado de ánimo (Sanz, 1991, como se cita en Espada-Largo & Cano-Vindel, 1999); juego patológico (García, Díaz & Aranda, 1993) El STAI evalúa dos dimensiones: ansiedad estado y ansiedad rasgo. Consta de 40 ítems, 20 por cada factor.…”
Section: )unclassified
“…These studies will provide the bases for future uses and it is quite reasonable to propose that many new applications will be found in the near future. In this sense, Arriagada et al [8] recently suggested an antagonistic activity in C. rigida when grown in the olive residues against Verticillium dahliae, a pathogen of tomato, though more investigation is still necessary.…”
Section: Future Perspectivesmentioning
confidence: 99%